Transformational, Visionary, and Prophetic Leadership: Their Impact on Teacher Job Satisfaction in Madrasa Ibtidaiyah - Juhji, Juhji; Maysaroh, Siti; Umi Prihatini , Hikmah (STAI Terpadu Yogyakarta, 2024)
This study aims to analyze the effect of prophetic, visionary, and transformational leadership styles simultaneously on madrasa ibtidaiyah teachers' job satisfaction. The research method uses quantitative methods with survey techniques. This study was conducted on madrasa ibtidaiyah teachers who became science facilitators, both provincial facilitators and regional facilitators, spread across 27 provinces. Two hundred ninety-one teachers were randomly selected using the random sample technique, and 179 were involved in this study. The research instrument used a validated questionnaire. Data analysis used inferential statistics with regression techniques. The results showed that rx123y was 0.532. The findings of this study indicate a strong and significant effect of prophetic leadership, visionary leadership, and transformational leadership simultaneously on the job satisfaction of madrasa ibtidaiyah teachers. The findings provide recommendations that madrasa ibtidaiyah teachers' job satisfaction can be improved simultaneously through prophetic, visionary, and transformational leadership.